In the Beginning of the Relationship Portugal - Lithuania: Martin Lopes and Damiano de Gois. Two Portuguese of XVI century in Lithuania - Julieta Maria Aires de Almeida Araujo e Esteves (Lietuvos Istorijos Studijos)
-